2020
DOI: 10.5799/jmid.700518
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Sentinel Seroprevalence, Cape Coast, Ghana

Abstract: Objectives: Sentinel studies have targeted prenatal women as they are largely descriptive of the reproductive bracket, and prevalence data may be extended to the general population. This study determined the seroprevalence of hepatitis C virus (HCV) infection among pregnant women attending antenatal clinic at the Cape Coast Metropolitan Hospital.Methods: Whole blood samples were collected from 258 pregnant women aged between 15-45 years, from September 1st through December 31st, 2018. Separated plasma was stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Previous systematic review reported HCV prevalence of 3% in Ghana with a recent nationwide auditing of hospital records estimating the prevalence at 4.6% (Agyeman et al, 2016; Nartey et al, 2023). The proportion from our study with HCV seropositive of 1.85% was less than these estimates but closer to the prevalence of 2.7% reported by a study undertaken previously in Cape Coast, the locale for our study (Tetteh et al, 2020). Because 30% of HCV serologically positive patients do not need treatment, treatment eligibility is based on detection of HCV ribonucleic acid (RNA) in patient serum (Patel et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous systematic review reported HCV prevalence of 3% in Ghana with a recent nationwide auditing of hospital records estimating the prevalence at 4.6% (Agyeman et al, 2016; Nartey et al, 2023). The proportion from our study with HCV seropositive of 1.85% was less than these estimates but closer to the prevalence of 2.7% reported by a study undertaken previously in Cape Coast, the locale for our study (Tetteh et al, 2020). Because 30% of HCV serologically positive patients do not need treatment, treatment eligibility is based on detection of HCV ribonucleic acid (RNA) in patient serum (Patel et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…reported by a study undertaken previously in Cape Coast, the locale for our study (Tetteh et al, 2020). Because 30% of HCV serologically positive patients do not need treatment, treatment eligibility is based on detection of HCV ribonucleic acid (RNA) in patient serum (Patel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A further mode of HCV spread may be through vertical transmission from pregnant women to their babies. Studies among pregnant women have demonstrated seroprevalence data ranging from 2.7% in the Central region [42] to 7.7% in a study in the Ashanti region [23]. Although anti-HCV testing is recommended as part of routine antenatal care screening in Ghana, this test is not free in many public health facilities, and a proportion of pregnant women may not be able to pay out-of-pocket.…”
Section: Plos Onementioning
confidence: 99%